Mathematical modeling of pollutants' migration from environmentally hazardous facilities considering surface water flow and infiltration - P. K. Shalkevich; S. P. Kundas; I. A. Gishkeluk (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
A mathematical model of pollutants' migration from environmentally hazardous facilities considering surface water flow and infiltration is developed. The methods for the numerical solution of differential equations describing the transport of pollutants and their entry into the groundwater from the surface of the soil due to the infiltration of precipitation are introduced. The developed mathematical model was implemented with the use of MATLAB and COMSOL software.